Building Knowledge Sharing Through Self-Efficacy and Organizational Citizenship Behavior - Sri Raharso (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The purpose of this paper is to examine the effect of self-efficacy and organizational citizenship behavior (OCB) on the knowledge-sharing behavior of minimarket employees. This behavior is needed so that minimarket employees can cooperate with colleagues, solve work problems, develop new ideas, and implement policies or procedures effectively and efficiently. However, research that focuses on retail business in minimarket format is still rarely done. This research is based on a survey of 151 minimarket personnel in Sarijadi Village and surrounding areas, employed incidental sampling. Multiple regression is used to test the hypothesis. The result of the regression analysis indicated that self-efficacy and OCB significantly independently and jointly predicted knowledge-sharing behavior. These findings imply that self-efficacy and OCB played important roles in knowledge-sharing behavior in the minimarket.